Is Motivation Really Important? Exploring Teachers' Need Satisfaction and Work Motivation through Organizational Climate and Psychological Capital - Utomo, Hanggara Budi; Ratnawati, Vivi; Ridwan, Ridwan; Syaharani, Duanty (Journal of Educational, Health and Community Psychology, 2024)
The teaching profession is a critical cornerstone for the success of education in Indonesia. However, maintaining teachers' work motivation poses a significant challenge, particularly in rural areas. This study examines the influence of organizational climate and psychological capital on teachers' work motivation, with need satisfaction serving as a mediating factor. Data were collected from 210 teachers in rural schools using a self-report survey and a convenience sampling technique. Participants completed scales measuring organizational climate, psychological capital, need satisfaction, and intrinsic motivation (interest/pleasure subscale). The study employed quantitative methods, including descriptive analysis of respondent profiles, measurement model analysis, and structural model analysis. Findings from structural equation modeling revealed that both organizational climate and psychological capital significantly influence teachers' work motivation, with need satisfaction acting as a crucial mediator. Organizational climate, as an external factor, significantly impacts need satisfaction and work motivation. Meanwhile, psychological capital, an internal factor, serves as a primary source of need satisfaction, which, in turn, plays a pivotal role in fostering work motivation. These findings underscore the importance of cultivating a supportive work climate and fostering psychological capital to enhance teachers' sense of responsibility and resilience in addressing the complexities of teaching in rural settings. The study highlights the need for a self-determination-oriented teacher culture in rural schools to sustain motivation and improve educational outcomes.